Determinants on balance of trade: a comparison between Malaysia and China / Nabila Ismail and Siti Nor Farhanim Mohmad Yusof - Ismail, Nabila; Mohmad Yusof, Siti Nor Farhanim (Faculty of Business and Management, 2016)
The importance of the trade balance is to determine the sound financial structure of a country. In fact, trade balance is also one of the main contributors towards the strength or weakness of the country’s economy growth. Therefore, this research is attempting to examine the relationship between exchange rate, foreign direct investment and gross domestic products with trade balance in both Malaysia and China. Statistical technique of Multiple Linear Regression was applied in this research by using annually time series data for the period of 1984 to 2013 in order to investigate the most significant factor that affecting the balance of trade in Malaysia and China. The result revealed from this research indicates that there is a positive significant relationship between gross domestic product and trade balance for both Malaysia and China while there is a negative significant relationship between foreign direct investment with trade balance in Malaysia and insignificant relationship between foreign direct investment with trade balance in China. In addition, the result for the real effective exchange rate and trade balance for both countries which is Malaysia and China showed the insignificant relationship between these variables. Last but not least, the gross domestic product is the most influential factor that affecting the balance of trade in Malaysia and China.